Student Problems in Learning Arabic at Senior High Schools - Langputeh, Sukree; Oktavia, Gifa; Febriani, Afifah; Pasaleron, Roni; Guslianto, Guslianto; Hamdi, Hafizul; Fitri, Rika (Al-Hashif: Jurnal Pendidikan dan Pendidikan Islam, 2023)
Arabic is a subject that must be studied in Islamic High Schools in Indonesia. However, in reality there are still students who have not mastered the rules of learning Arabic, because there are several problems. This research aims to find out what problems students actually experience in learning Arabic. This research uses qualitative methods with a case study approach (case study design). Data sources were taken from twenty informants consisting of school principals, teachers and students through individual and group interviews. To strengthen the interview data, the author also made direct observations of teachers and students. All interview and observation data were analyzed using the Miles & Huberman model Analysis Interactive. Research findings found that there were five problems in learning to learn Arabic in high school. The five problems are: i) students' previous educational background, ii) inadequate facilities and infrastructure, iii) there is still a culture of teasing, iv) students are lazy about learning and v) the way teachers teach does not attract students' attention. The results of this research can be used as initial data for future researchers to study this problem in different contexts and problems.